PERILAKU PENCEGAHAN STUNTING PADA IBU HAMIL TRIMESTER II DI BPM BUKITTINGGI - Media Fitri; Yellyta Ulsafitri; Desi Andriani (HUMAN CARE JOURNAL, 2023)
Stunting is a condition of failure to thrive in children (infants under five years) caused by chronic malnutrition so that children are too short for their age. Malnutrition can occur since the baby is in the womb and in the early days after the baby is born. The purpose of this study was to determine stunting prevention behavior in Trimester II pregnant women at BPM Kota Bukittinggi in 2022. This research is a descriptive study that describes a state of behavior of pregnant women in preventing stunting in toddlers at BPM Bukittinggi city. The population in this study were Trimester II pregnant women who checked themselves at BPM Bukittinggi City. Sampling by accidental sampling. The results showed that most pregnant women always behaved in coming to the village midwife, met their nutritional needs, always consumed iron, and behaved to avoid exposure to cigarette smoke. It is hoped that midwives can improve the form of promotion on how to consume iron supplement tablets so that the behavior of pregnant women consuming FE tablets is appropriate.Keywords : Stunting, Pregnant Women, Trimester II